MODEL DESAIN PRAKTIK UPCYCLING FASHION DALAM PEMANFAATAN LIMBAH PAKAIAN BEKAS - Annesha, Bella; Titisari, Bintan (ATRAT: Jurnal Seni Rupa, 2023)
The fashion industry tends to move quickly to follow the latest fashion trends and has an impact on the large amount of clothing textile waste, both from production and from clothes. One of the efforts to minimize this impact is to extend the outdated clothes. There are more emerging Indonesian fashion brand nowadays that apply upcycle processing as one of their product development, especially in big cities such as Bandung and Jakarta. The finding of this is a model that shows upcycling process has similar stages: research idea & concept, design & production, post production, and selling, furthermore, aspects that influence the process are also being anaylised. The results of the analysis are processed into a model for the development of upcycle fashion practices where the making of this design practice model is intended so that fashion actors and also ordinary people who want to implement upcycle can adapt this practice model. Keywords: Upcycle, Design process, Second-hand clothes, Sustainable ------------------------------------------------------------------------------------ Industri fashion cenderung bergerak cepat mengikuti tren fashion terkini dan berdampak pada banyaknya limbah tekstil pakaian, baik dari produksi maupun dari pakaian yang sudah tidak terpakai. Salah satu upaya untuk meminimalisasi dampak tersebut adalah dengan memperpanjang masa pakai pakaian yang sudah usang. Semakin banyak bermunculan brand fashion Indonesia yang menerapkan proses upcycle sebagai salah satu pengembangan produknya, terutama di kota-kota besar seperti Bandung dan Jakarta. Temuan ini adalah model yang menunjukkan proses upcycle memiliki tahapan yang sama: riset ide & konsep, desain & produksi, pasca produksi, dan penjualan. Selain itu aspek-aspek yang mempengaruhi proses juga dianalisis. Hasil analisis diolah menjadi model pengembangan praktik fashion upcycle dimana pembuatan model praktik fashion ini dimaksudkan agar para pelaku fashion dan juga masyarakat awam yang ingin menerapkan upcycle dapat mengadaptasi model praktik ini. Kata Kunci: Upcycle, Proses desain, Pakaian second-hand, Sustainable